Self-reported factors associated with engagement in moderate to vigorous physical activity among elderly people: A population-based study - Ramin Shiraly; Zahra Shayan; Vahid Keshtkar; Mehdi Hamed (International Journal of Preventive Medicine, 2017)
Background: Physical activity (PA) typically decreases with aging, especially of moderate to vigorous level, and this change affects health outcomes of older adults. Age-related decline is not evenly distributed across elderly population and is attributed to psychosocial, physical, and environmental determinants. Methods: We selected a sample of 1000 elderly people from urban parts of Shiraz in Southern Iran with a two-stage random sampling procedure. Self-reported PA data and correlates of moderate to vigorous activity were collected by interview with the respondents from selected households. Bivariate associations were examined using Chi-square test. Log-binomial regression was used to weigh variables associated with more than light PA. Results: Some demographic variables (older age, female sex, lower education level, retirement, and single or widowed status), health problems (lower extremity pain and hypertension), and psychosocial factors (lack of motivation, fear of injury, unsafe roads, and daily life problems) were potential correlates of inadequate PA with bivariate analysis. In log-binomial regression model, lack of motivation (adjusted prevalence ratio [APR] = 2.11, 95% confidence interval [CI]: 1.25–3.56), daily life problems (APR = 1.82, 95% CI: 1.26–2.62), lower educational level (APR = 1.64, 95% CI: 1.08–2.49), unsafe roads (APR = 1.59, 95% CI: 1.02–2.49), and knee pain (APR = 1.68, 95% CI: 1.09–2.58) were associated with lower engagement in moderate to vigorous PA among Iranian older adults. Conclusions: Psychosocial attributes considerably influence PA behaviors in older adults. Lower extremity joint pain is a key medical concern. Interventions to promote PA among older adults should be multilevel and particularly targeting personal psychosocial factors.